السباحة - بلخير ، عبدالقادر (Mohamed Boudiaf University of M'Sila, 2023)
الملخص: بالعربية : تعتبر الرياضة بشكل عام والسباحة بشكل خاص نموذج مصغر لما هو متوقع ان يحدث في مجتمع مستقبل مما لا شك فيه ان السباحة تعتبر قاعدة هامة وضرورية بالنسبة لممارسها وتسمح لهم بالنمو السوي في وسط المجتمع. والسباحة ليست وليدة الظهور بل واكبت عصور وامم ومجتمعات ولهذا سنحاول في هذا البحث سرد التطور التاريخي للسباحة من الانسان البدائي الى غاية المجتمعات الحديثة بالشكل المتعارف عليه حاليا ومع تطور المجتمع من جميع نواحيه سواء اقتصاديا او اجتماعيا او ثقافية او حتى التكنولوجيا تطورت السباحة وسيارة الركب الحضارية الى ان اصبحت عليه الان بشكلها المختلف وانواعها المتداولة، وكذا تداخل كل من العلوم التربوية النفسية وعلم الميكانيك والحركات والاداء المهاري للسباحة ومجمل القوانين التي لها تأثير كبير في تحسين وتطور السباحة. Searchlight in English Sports in general and swimming in particular are a miniature model of what is expected to happen in a future society. There is no doubt that swimming is an important and necessary foundation for its practitioners and allows them to grow properly in the midst of society. Swimming is not a new phenomenon, but has accompanied ages, nations and societies. Therefore, in this research, we will try to narrate the historical development of swimming from primitive man to modern societies in the form currently known. With the development of society in all its aspects, whether economic, social, cultural or even technological, swimming and the civilized car of the car have developed until it has become what it is now in its different form and common types, as well as the overlap of educational and psychological sciences, mechanics, movements and skillful performance of swimming and all the laws that have a great impact on improving and developing
Keywords: السباحة الحرة; السباحة على الصدر; السباحة على الضهر